OUTCOMES OF INTENSIVE CARE PATIENTS HAVING SEPTIC SHOCK AT A TERTIARY CARE HOSPITAL OF ISLAMABAD - Ali, Azmat; Abbasi, Awais Saeed; Sheikh, Maliha (Journal of Ayub Medical College Abbottabad, 2017)
Background: Septic shock is defined as sepsis with circulatory, cellular and metabolic abnormalities which are associated with greater mortality more than 40%. The objective of this study was to identify shortcomings and act promptly and adequately. Methods: This case series included 32 patients over a period of 03 months, September to November 2016 done at ICU of KRL Hospital Islamabad. Results: The study only enrolled patients who fulfilled the criteria of septic shock. Mortality was as high as 50%. (UTI) was the most common infection (43.75%). In patients who died Pneumonia was commonest infection (43.75%). Mean TLC, CRP and lactate was 17.48Ã—109/l, 29.28 mg/L and 6.81mmom/L respectively. Escherichia Coli (E. coli) was the most common isolated pathogen (31.25%) followed by Staphylococcus Aureus (12.5%). Mean initial MAP was 49.7 mmHg and mean MAP at end of 3-day period was 71.4 mmHg. Mean norepinephrine dose given on day 1, 2 & 3 was 0.90 µg/kg/min, 1.01 µg/kg/min & 1.28 µg/kg/min respectively. Mean hospital stay was 7.1 days. Six out of 08 (75%) patients who needed ventilator support died while 02 out of 08 (25%) patients survived. Acute Kidney Injury (AKI) was the most common End Organ Damage (EOD). Conclusion: Mortality remains high in septic shock despite maximum efforts. In current study MAP, serum lactate level, hospital stay, need for ventilator support, comorbidities, need for newer generation antimicrobials were the important cofounders in differentiating patients who died and those who survived with significant p-values in the 1st four conditions. Keywords: Sepsis; Septic Shock; Infection; TLC; CRP; serum Lactate; Norepinephrine; Multi Organ Failure (MOF); MAP; Antimicrobials